Dampak Komitmen Organisasi dan Kepuasan Kerja terhadap Turnover Intention: Studi Empiris pada Karyawan bagian Operator di Salah Satu Perusahaan Garment di Cimahi - Novita Sidharta; Meily Margaretha (Jurnal Manajemen Maranatha, 2011)
This study was conducted to investigate the impact of organizational commitment and job satisfaction to turnover intention felt by the operator employees' one of Garment Company in Cimahi. Data were collected through survey and bibliography study. The questionnaires have send to 150 respondents and one hundred and forty seven were returned yielding response rate 98%. From the correlation and regression analysis, the study found that the correlation and the impact of turnover intention has supported. From four hypotheses that have tested in this study, all hypotheses were supported. The result showed that organizational commitment and job satisfaction were negatively and significantly related to turnover intention and having negative influence on it.Keywords: organizational commitment, job satisfaction, turnover intention